• 2022-06-03
    对下面的每一对项,可合一的是:( )
    A: (f Marcus (g x y)) (f x (g Caesar Marcus))
    B: (f x) (f (g y))
    C: (f Marcus) (f Caesar)
    D: (f y) (f Caesar)
  • B,D

    内容

    • 0

      谓词公式($x)F(x) Þ ($x)G(x)的前束范式是( )。 A: ("x)("y) (F(x) Þ G(y)) B: ($x)("y)(F(x) Þ G(y)) C: ("x)($y) (F(x) Þ G(y)) D: ($x)($y)(F(x) Þ G(y))

    • 1

      Ø"xF(x)® $yG(y)的前束范式是( ) A: "x$y(Ø F(x) ® G(y)) B: "x"y(Ø F(x) ® G(y)) C: $x"y(Ø F(x) ® G(y)) D: $x$y(Ø F(x) ® G(y))

    • 2

      "x F(x,y) → ¬ $y G(x,y)的前束范式 A: $x$y(F(x,m) ®Ø G(t,y)) B: $x∀y(F(x,m) ®Ø G(t,y)) C: ∀x$y(F(x,m) ®Ø G(t,y)) D: ∀x$y(F(x,m) ® ØG(t,y))

    • 3

      以下哪个不是谓词公式? A: F(x) B: F(x)ØÚG(x,y) C: "x(F(x)®G(x)) D: $x"y(F(x)®G(y)ÙL(x,y))

    • 4

      以下哪个不是谓词公式? A: F(x) B: F(x)ØÚG(x,y) C: "x(F(x)®G(x)) D: $x"y(F(x)®G(y)ÙL(x,y))